Centromeric enrichment of LINE-1 retrotransposons and its significance for the chromosome evolution of Phyllostomid bats - de Sotero-Caio, Cibele Gomes; Cabral-de-Mello, Diogo Cavalcanti [UNESP]; Calixto, Merilane da Silva; Valente, Guilherme Targino [UNESP]; Martins, Cesar [UNESP]; Loreto, Vilma; de Souza, Maria José; Santos, Neide (Springer Nature, 2017)
Despite their ubiquitous incidence, little is known about the chromosomal distribution of long interspersed elements (LINEs) in mammalian genomes. Phyllostomid bats, characterized by lineages with distinct trends of chromosomal evolution coupled with remarkable ecological and taxonomic diversity, represent good models to understand how these repetitive sequences contribute to the evolution of genome architecture and its link to lineage diversification. To test the hypothesis that LINE-1 sequences were important modifiers of bat genome architecture, we characterized the distribution of LINE-1-derived sequences on genomes of 13 phyllostomid species within a phylogenetic framework. We found massive accumulation of LINE-1 elements in the centromeres of most species: a rare phenomenon on mammalian genomes. We hypothesize that expansion of these elements has occurred early in the radiation of phyllostomids and recurred episodically. LINE-1 expansions on centromeric heterochromatin probably spurred chromosomal change before the radiation of phyllostomids into the extant 11 subfamilies and contributed to the high degree of karyotypic variation observed among different lineages. Understanding centromere architecture in a variety of taxa promises to explain how lineage-specific changes on centromere structure can contribute to karyotypic diversity while not disrupting functional constraints for proper cell division.
Keywords: centromere; Chiroptera; karyotype; non-LTR; Phyllostomidae; transposable element